2019
DOI: 10.5194/acp-19-2833-2019
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the catalytic role of oxalic acid in SO<sub>3</sub> hydration to form H<sub>2</sub>SO<sub>4</sub> in the atmosphere

Abstract: Abstract. The hydration of SO3 plays an important role in atmospheric sulfuric acid formation. Some atmospheric species can be involved in and facilitate the reaction. In this work, using quantum chemical calculations, we show that oxalic acid, the most common dicarboxylic acid in the atmosphere, can effectively catalyze the hydration of SO3. The energy barrier of the SO3 hydration reaction catalyzed by oxalic acid (cTt, tTt, tCt and cCt conformers) is a little higher or less than 1 kcal mol−1, which is lower … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 64 publications
4
18
0
Order By: Relevance
“…charge and H2, H4 atom gains the charge by 0.04 and 0.01 a.u., respectively with respect to I1. The redistribution of electronic charge on the reactive species shows that the mechanism proposed in this study takes place through hydrogen atom transfer reaction, which is in accordance with previous study on hydrogen atom transfer reaction for closed shell system . In the transition state, TS1‐di, the oxygen atom O2 of second water molecule starts to bind with S atom of HNSO 2 with S‐O2 distance of 1.8 Å.…”
Section: Resultssupporting
confidence: 90%
“…charge and H2, H4 atom gains the charge by 0.04 and 0.01 a.u., respectively with respect to I1. The redistribution of electronic charge on the reactive species shows that the mechanism proposed in this study takes place through hydrogen atom transfer reaction, which is in accordance with previous study on hydrogen atom transfer reaction for closed shell system . In the transition state, TS1‐di, the oxygen atom O2 of second water molecule starts to bind with S atom of HNSO 2 with S‐O2 distance of 1.8 Å.…”
Section: Resultssupporting
confidence: 90%
“…The structures of the reactant (RC), product (PC), intermediate (IM), and transition states (TS) are optimized using M06-2X density functional method with the 6-311++G (d, p) basis set [37]. This is relatively accurate and time-efficient when used to study the reaction mechanism and has been employed successfully in our previous studies [38,39]. The vibrational frequencies have been obtained to verify that the reactant complexes, intermediates, and product complexes have all positive frequencies and that the transition state (TS) geometries have only one imaginary frequency at the same level.…”
Section: Methodsmentioning
confidence: 99%
“…Plentiful computational studies have also shown that DHAT reactions result in a catalytic effect. Examples include: (i) gas‐phase hydrolysis of HFCO is catalyzed by H 2 SO 4 ; (ii) decomposition of CF 3 OH is catalyzed by formic acid; (iii) SO 3 hydration is catalyzed by oxalic acid; (iv) SO 3 +NH 3 reaction is catalyzed by NH 3 , etc. Furthermore, double H‐atom exchange reactions of HO 2 +HX (X=F, Cl, Br, I) have also been predicted computationally …”
Section: Figurementioning
confidence: 99%